Farmer to Farmer Extension for Sustainable Agriculture an Experience of U.P. Sodic Lands Reclamation Project - India - R.S. Saxena,; S.K. Pradhan, (Journal of Agricultural Extension Management, 2025)
India ha around 0.73 % of the sodic lands around the world. The state of Uttar Pradesh in Indi a has some 1.2 million ha. of sodic waste lands. Such areas account for 10% of total cultivable area of the state and about 17 % of the salt affected lands in the country